2004
DOI: 10.1128/mcb.24.19.8342-8355.2004
|View full text |Cite
|
Sign up to set email alerts
|

Swi1 and Swi3 Are Components of a Replication Fork Protection Complex in Fission Yeast

Abstract: Swi1 is required for programmed pausing of replication forks near the mat1 locus in the fission yeast Schizosaccharomyces pombe. This fork pausing is required to initiate a recombination event that switches mating type. Swi1 is also needed for the replication checkpoint that arrests division in response to fork arrest. How Swi1 accomplishes these tasks is unknown. Here we report that Swi1 copurifies with a 181-amino-acid protein encoded by swi3؉ . The Swi1-Swi3 complex is required for survival of fork arrest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
315
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(343 citation statements)
references
References 69 publications
27
315
0
1
Order By: Relevance
“…Fission yeast Swi1 and Swi3 proteins (orthologs of Tof1 and Csm3 in budding yeast, and Timeless and Tipin in mammals, respectively) form a fork protection complex, and their mutants accumulate Rad52 foci during unperturbed replication, probably as a consequence of ssDNA gaps formed near replication forks (Noguchi et al 2004). In swi1D and swi3D, we found similar Rad52 peak patterns as those in hst4D (Fig.…”
Section: Rad52 Enrichment Patterns In Pfh1 Helicase Mutantssupporting
confidence: 64%
“…Fission yeast Swi1 and Swi3 proteins (orthologs of Tof1 and Csm3 in budding yeast, and Timeless and Tipin in mammals, respectively) form a fork protection complex, and their mutants accumulate Rad52 foci during unperturbed replication, probably as a consequence of ssDNA gaps formed near replication forks (Noguchi et al 2004). In swi1D and swi3D, we found similar Rad52 peak patterns as those in hst4D (Fig.…”
Section: Rad52 Enrichment Patterns In Pfh1 Helicase Mutantssupporting
confidence: 64%
“…Our studies have shown that depletion of human Tipin or Timeless yields very similar phenotypes. Several studies have also demonstrated that Tof1/Swi1 and Csm3/Swi3 mutants share very similar phenotypes in yeast (12,14,15,21,23,24,30). This could be explained if it is the function of the complex that is required for each of these functions.…”
Section: Depletion Of Either Tipin or Timeless Leads To The Loss Of Bothmentioning
confidence: 99%
“…The homologs of Tipin have been identified as Csm3 in budding yeast and Swi3 in fission yeast (9,18). Like their mammalian counterpart, Csm3 and Swi3 have been shown to interact with Tof1 and Swi1, respectively, and are also required for activation of Rad53 and Cds1 in response to HU (19)(20)(21)(22)(23)(24). Like Tof1, Csm3 was found to be required for the pausing of replication forks at replication fork barriers and site-specific replication termini in yeast (15,25).…”
mentioning
confidence: 99%
“…3,6,8,11 Tim-Tipin and Claspin likely work together to mediate ATR activation of Chk1 by Tipin-RPA recruitment of ClaspinChk1 through a Tipin-Claspin interaction. 8 Furthermore, TimTipin and Claspin orthologs/analogs associate with chromatin, interact with replisome components and appear to travel with replication forks in the absence of exogenously applied DNA damage, 9,10,[12][13][14][15][16] and DNA synthesis is compromised when human cells are depleted of Timeless, Tipin or Claspin. 3,6,17 Timeless, Tipin and Claspin orthologs/analogs also contribute to sister chromatid cohesion (SCC) in various organisms.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 SiRNA-mediated reduction of Timeless, Tipin or Claspin proteins attenuates DNA damageinduced phosphorylation of Chk1 and compromises ultraviolet (UV) light-induced activation of the intra-S checkpoint in HeLa cells. 3,6,8,11 Tim-Tipin and Claspin likely work together to mediate ATR activation of Chk1 by Tipin-RPA recruitment of ClaspinChk1 through a Tipin-Claspin interaction.…”
Section: Introductionmentioning
confidence: 99%